1995
DOI: 10.1007/bf00210304
|View full text |Cite
|
Sign up to set email alerts
|

Germline mosaicism for an alanine to valine substitution at residue ? 140 in hemoglobin Puttelange, a new variant with high oxygen affinity

Abstract: Hb Puttelange [beta 140(H18)Ala-->Val] was found as a de novo mutation in two siblings of a French family suffering from polycythemia. Both parents were phenotypically normal and exclusion of paternity has been ruled out by the study of several polymorphic markers located on different chromosomes. The structural modification of Hb Puttelange was established by reversed-phase HPLC analysis of the tryptic digest of the abnormal chain. The amino acid composition of an abnormal beta T14 peptide revealed that one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…The first example of a Hb variant causing erythrocytemia was reported in 1966 (14). Currently, more than 200 articles related to Hb variants with increased oxygen affinity have been published (14)(15)(16)(17)(18)(19)(20)(21)(22)(23). We confirmed that the Hb KSVGH patient has PV due to the high WBC and PLT, and low EPO values.…”
Section: Discussionsupporting
confidence: 89%
“…The first example of a Hb variant causing erythrocytemia was reported in 1966 (14). Currently, more than 200 articles related to Hb variants with increased oxygen affinity have been published (14)(15)(16)(17)(18)(19)(20)(21)(22)(23). We confirmed that the Hb KSVGH patient has PV due to the high WBC and PLT, and low EPO values.…”
Section: Discussionsupporting
confidence: 89%
“…To our knowledge, there is only one previously reported case of germ line mosaicism that affects globin genes. Haemoglobin Punttelange [β140 Ala→Val] was found as a de novo mutation in two French siblings suffering from polycythemia, of which both parents were phenotypically normal and had no detectable alterations in the β‐genes (15). In this case, the mutation seemed to have arisen in the germ line cells of the father of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…If this mutation occurred during meiosis process or as an early post-zygotic event in the proband the risk would be negligible. In contrast, the risk increases significantly if the mutation occurred during an early germ line mitotic division, and one of the parents is a germinal mosaic [22,23]. In theory, the maximum risk for future pregnancies after the birth of one affected child to unaffected parents is 4.8% [23].…”
Section: Discussionmentioning
confidence: 99%